CHARACTERISTICS OF A LEADERSHIP DEVELOPMENT PROGRAM PILOT RESEARCH AT A HUNGARIAN SME OPERATING IN THE ICT SECTOR - Judit TÖRÖK-KMOSKÓ; Krisztina DAJNOKI (Annals of the University of Oradea: Economic Science)
The current research reports on a pilot study that was conducted to test the feasibility of a larger study exploring a leadership development program at a small and medium-sized enterprise (SME) in the ICT (Infocommunications) sector in Hungary. The study employed a mixed-methods approach to data collection, which included literature review, document analysis, and structured interviews with various participants involved in the leadership development program. The literature review focused on the history, current state, existing gaps and limitations, and theoretical frameworks and concepts related to the research topic. The document analysis aimed to gain an in-depth understanding of the research topic and complement the findings from the literature review. The structured interviews were designed to be consistent and standardized, with a pre-determined set of questions asked to each participant. The interviews were conducted with a diverse group of participants, including the CEO, People Development Manager, Hiring managers, Domain Engineering Leads, the Human Resources team, and participants of the leadership development program.